XXV ENMC / XIII ECTM / 9º MCSul / IX SEMENGO - Buske, Daniela (Ciência e Natura, 2023)
In 2022, the events XXV National Meeting of Computational Modeling (XXV ENMC) and XIII Meeting of Science and Technology of Materials (XIII ECTM) took place from October 19 to 21, 2022, with all activities of the event carried out in the webinar modality. In this particular year, together with the XXV ENMC and the XIII ECTM, the 9th Southern Conference on Computational Modeling (9th MCSul) and the IX Seminar and Workshop on Ocean Engineering (IX SEMENGO) were held, providing the opportunity to bring together researchers from related areas of knowledge. The events included lectures from the area of Computational Modeling in Brazil and abroad; its organization was the result of a collaboration between professors from ten public teaching institutions in the country, under the coordination of researchers from universities in Rio Grande do Sul; the event had more than 250 manuscripts submitted and presented in 57 technical sessions, with emphasis on the contributions made by graduate students. The Organizing Committee selected a sample of original works presented at the event with an interdisciplinary theme. This led to the publication, in December 2023, of this special edition of the XXV ENMC / XIII ECTM / 9º MCSul / IX SEMENGO. We thank the authors who contributed to the high level of this edition. We wish you all a pleasant reading.